ANALISIS PENGARUH PENGAWASAN MANAJEMEN SERTA MOTIVASI KERJA TERHADAP KINERJA PEKERJA DI PT ABC - Novendra, Muhammad Racha; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
This research is to find out and analyze the impact of Management Supervision and Work Motivation on Employee Performance. This research was conducted at PT ABC from March 2023 to July 2023. In this study, the population was all employees, totaling 150 people. The independent variables in this study: Management Supervision (X1) and Work Motivation (X2) and the dependent variable is Employee Performance (Y). Data analysis method used in this research is simple linear analysis. The results of the study are Management Supervision and Work Motivation have an influence on Worker Performance of 18.1%.